2017
DOI: 10.1177/1747954117710509
|View full text |Cite
|
Sign up to set email alerts
|

Bench behaviour of ice hockey coaches: Psychophysiological and verbal responses to critical game incidents

Abstract: The purpose of this study was to examine coaches' psychophysiological and verbal responses to different game situations. The in-game heart rate and verbal responses of three elite ice hockey coaches to four critical game incidents (Goals For/Against; Penalties Taken/Drawn) over four university women's games were assessed. Verbal comments were categorised using the Coach Behaviour Assessment System, and then comments and heart rate were sequenced to critical incidents recorded on video review. Overall, in-game … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 17 publications
0
8
1
Order By: Relevance
“…Unlike earlier studies, Kennedy and Knight 11 found that general feedbacks accounted for the largest percentage of all feedback given throughout the games. While they found silence to be a relatively rare event, their further analysis revealed various patterns of feedback among coaches.…”
Section: Introductioncontrasting
confidence: 75%
See 3 more Smart Citations
“…Unlike earlier studies, Kennedy and Knight 11 found that general feedbacks accounted for the largest percentage of all feedback given throughout the games. While they found silence to be a relatively rare event, their further analysis revealed various patterns of feedback among coaches.…”
Section: Introductioncontrasting
confidence: 75%
“…Although this tendency was seen to a certain degree, the results were not significant. Studies have found that focused feedback emerges as a result of coaches' strategic analysis 3,6,11,17,26 , whereby they are the result of intensive thinking and they contain specific information. These two components sharpen the information that is passed on to the athletes, lowers their cognitive load, and may improve their performance.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Based upon extensive data analysis, we will discuss how an increase in the volunteer coach knowledge, width and depth of the coaching experience via education programs, communities of practice, mentoring and reflective practice can shorten the learning curve of coach developmentskills need to first be developed and practiced, then supported and valued for coaches to continue beyond the learning stage. Half-time (HT) is a crucial in-competition period and an important component of a coach's performance strategy (Kennedy & Knight 2017). This period represents a complex and pivotal time (Mouchet & Duffy 2020) when coaches interact with athletes and multiple staff members (Allain et al, 2018).…”
Section: Presenter Biographymentioning
confidence: 99%